The Political Economy of Public Reform Adoption: Patterns in Twenty Indonesian Districts. Issue 4 (1st October 2016) - Wetterberg, Anna; Brinkerhoff, Derick W.
ABSTRACT: New Public Management (NPM) reforms are often perceived as technical, with little attention to political and institutional factors. Comparing choices in 20 Indonesian districts, we explore which of four political economic factors influence uptake of NPM-based service delivery reforms. We find that democratic political competition laid the groundwork for political alliances, patterns of patronage, and party provision of benefits that condition reform choices. State-led policy entrepreneurship was evident from education agency technocrats. Public sector modernization may have increased orientation towards performance, with education reforms adopted by districts already achieving relatively good sectoral results. Health reforms were more common in districts providing greater opportunities for citizen participation . The complex interactions among the factors argue for working within these realities, rather than seeing them as impediments to be avoided in a drive for reforms. Education technocrats' dominance, bolstered by central policy priorities, argues for more nuanced mechanisms for meeting national goals to avoid crowding out responsiveness to local citizens.